Economics of Gap Planting Technology to Rehabilitate Degraded Natural Forests in Indonesia - Bintang Charles Hamonangan Simangunsong; Elias (Jurnal Sylva Lestari, 2026)
The economics of gap planting technology matter because they determine whether restoring degraded natural forests can be done at scale in a way that’s economically and financially viable for governments, communities, and investors, while also recovering biodiversity and ecosystem services. This study assessed the economic benefits of using gap planting technology —planting commercial, shade-intolerant tree species in artificial gaps— to rehabilitate degraded natural forests. A purposive sampling technique was used to establish 16 artificial gaps, each covering 2,000 m2, which were inventoried on four occasions. Based on the data, the mortality rate, diameter and height increments were determined. Net present value (NPV), internal rate of return (IRR), benefit-cost ratio (BCR), and land expectation value (LEV) were also determined in the economic analysis of three scenarios differentiated by rotation age of 6, 7, and 8 years. The results showed the average mortality, diameter and height increments were, respectively, 30%, 3.80 cm year-1 and 326.45 cm year-1. Assuming a real discount rate of 8% year-1 and a real stumpage price of IDR 0.75 million m-3, all scenarios showed NPV >= 0, BCR >= 1, IRR >= minimum acceptable rate of return (MAR), LEV > IDR 115 million ha-1, and job creation of 106 man-days ha-1. Moreover, NPV and LEV are more sensitive to changes in the real stumpage price than to changes in the real discount rate. It is concluded that gap planting technology with white jabon is financially and economically viable under these assumptions and is recommended for the rehabilitation of degraded natural tropical forests in Indonesia. Keywords: economic benefits, fast-growing species, forest rehabilitation, land expectation value, tree increment